The Indo-European name of the night (Atti del Sodalizio Glottologico Milanese, 2014)
The Greek word for ‘night’ nýx nyktós is in some details different from the common IE word, generally reconstructed as *nokut- or *nokt- (only Hitt. has a noun with different vocalism *nekuz ‘evening’ and a verb nekuzi ‘becomes evening’). An easily explanation of the different vocalism (u instead of o) can be proposed, if we suppose an intentional modification produced by linguistic taboo. The Greek forms with an aspirate (nykheúō, etc.) are to be considered as the continuation of a distinct root *neuguh-, also attested in the Armenian verb nnǰem ‘I sleep, I fall asleep’, possibly from *ni-nuguh-e-. KEYWORDS: Greek, Indo-European, etymology, night, linguistic taboo